Experimental investigation of particle deagglomeration using turbulence - Köksoy, Cagatay; Ertunc, Özgür; Hüttner, Sebastian; Wachtel, Herbert; Delgado, Antonio (Journal of Physics : Conference Series, 2011)
The effect of turbulence on powder aerosol deagglomeration was investigated. Two impinging jets were used to generate turbulence. Lactose particles, whose fully dispersed fine particle fraction (FPF) - number percentage of the particles whose diameter smaller than 5 μm- is above 90 %, were applied as aerosol powder. The particle size distribution after the dispersion unit were measured by using phase Doppler anemometer (PDA) and turbulence level were quantified at the impingement point of two jets with laser Doppler anemometer. As the turbulence level increases turbulent time and length scales decrease, and the ratio of fine particle fraction (FPF) increases from 36% to 86%.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.experi_1